2018
DOI: 10.1371/journal.pone.0196410
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid insecticides maintain repellent effect on knock-down resistant populations of Aedes aegypti mosquitoes

Abstract: Pyrethroid-treated clothing is commonly worn for protection against mosquitoes; pyrethroids are both insecticides and repellents. Pyrethroid resistance has become increasingly common in Aedes aegypti, the vector of dengue, Zika, and other arboviruses, but it is not clear whether resistance is associated with reductions in repellency. In order to determine whether long-lasting permethrin impregnated (LLPI) clothing is protective, we used Aedes aegypti from New Orleans, LA (pyrethroid-sensitive) and San Juan, PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 60 publications
0
34
1
5
Order By: Relevance
“…This result is similar to the lower repellency resistance observed in the PR strain to transfluthrin compared to metofluthrin observed in the present study. In contrast to these findings, a recent paper by Bowman et al . found that a Puerto Rico strain of Ae.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…This result is similar to the lower repellency resistance observed in the PR strain to transfluthrin compared to metofluthrin observed in the present study. In contrast to these findings, a recent paper by Bowman et al . found that a Puerto Rico strain of Ae.…”
Section: Discussionmentioning
confidence: 69%
“…32 This result is similar to the lower repellency resistance observed in the PR strain to transfluthrin compared to metofluthrin observed in the present study. In contrast to these findings, a recent paper by Bowman et al 22 found that a Puerto Rico strain of Ae. aegypti similar to the one used here carried kdr mutations, but showed no cross-resistance to repellency in arm-biting tests with permethrin, wileyonlinelibrary.com/journal/ps deltamethrin, and etofenprox, compounds acting via contact irritancy and not spatial repellency.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This translates into about 33 % disease prevalence and may be linked to factors such as pyrethroid resistance that might be impeding efficacy of the LLINs Pyrethroids exert their insecticidal effect on the voltage-gated sodium channel (VGSC) located on the membrane of neurons [14]. When pyrethroids bind an open channel, they block its closure, thus extending the action potential and resulting in the insect's rapid paralysis, a phenomenon known as "knockdown" (kdr) [15]. However, mosquito resistance to pyrethroids is an emerging challenge to efficacy of otherwise successful insecticide-treated nets (ITN) based malaria control intervention against adult vector [16].…”
Section: Introductionmentioning
confidence: 99%